Influence of management practices on strengthening university teaching commitment in the Peruvian context - Pérez-Mamani, Rubens Houson (2026)
Managerial management is a key factor in the organizational development of public universities due to its influence on teachers’ commitment, a fundamental element for ensuring the quality of the educational process. In the Peruvian context, limitations associated with leadership, planning, and institutional organization affect teaching commitment, making it necessary to analyze improvement strategies from a management perspective; therefore, the objective was to determine the influence of managerial management on university teachers’ commitment, with the intention of strengthening strategic planning, institutional organization, leadership, and control. A quantitative approach was used with a pre-experimental design; the sample consisted of 69 teachers, and the intervention focused on the faculty’s managerial team at a Peruvian public university; a Likert-scale questionnaire was administered, and Student’s t-test for related samples was applied. A significant difference was found between the pretest and posttest measurements of university teachers’ commitment (t = -12.291, p < 0.001), confirming the influence of managerial management; at the dimensional level, improvements were observed in commitment to students (t = -8.572, p < 0.001), commitment to teaching work (t = -6.088, p < 0.001), and commitment to the institution (t = -11.688, p < 0.001). It is concluded that managerial management influences university teachers’ commitment, and that interventions aimed at improving planning, organization, leadership, and control generate positive changes in faculty attitudes and behaviors.